2009
DOI: 10.1051/0004-6361/200911993
|View full text |Cite
|
Sign up to set email alerts
|

SN 1999ga: a low-luminosity linear type II supernova?

Abstract: Context. Type II-linear supernovae are thought to arise from progenitors that have lost most of their H envelope by the time of the explosion, and they are poorly understood because they are only occasionally discovered. It is possible that they are intrinsically rare, but selection effects due to their rapid luminosity evolution may also play an important role in limiting the number of detections. In this context, the discovery of a subluminous type II-linear event is even more interesting. Aims. We investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 96 publications
1
8
0
Order By: Relevance
“…Given this low luminosity and the presence of narrow P-Cygni Balmer lines in follow-up spectra, Bose et al (2017) identified Gaia16cfr as a likely SN impostor. NGC 2442 was the host of the peculiar low-luminosity SN II 1999ga (Pastorello et al 2009) as well as the SN Ia 2015F and had been observed with deep, multiband, multi-epoch HST imaging by Riess et al (2016), who derived a Cepheid distance modulus of m − M = 31.51 ± 0.05 mag (20.1 ± 0.5 Mpc). Fraser et al (2017) and Kilpatrick et al (2017) identified a counterpart to Gaia16cfr in pre-outburst HST images.…”
Section: Introductionmentioning
confidence: 99%
“…Given this low luminosity and the presence of narrow P-Cygni Balmer lines in follow-up spectra, Bose et al (2017) identified Gaia16cfr as a likely SN impostor. NGC 2442 was the host of the peculiar low-luminosity SN II 1999ga (Pastorello et al 2009) as well as the SN Ia 2015F and had been observed with deep, multiband, multi-epoch HST imaging by Riess et al (2016), who derived a Cepheid distance modulus of m − M = 31.51 ± 0.05 mag (20.1 ± 0.5 Mpc). Fraser et al (2017) and Kilpatrick et al (2017) identified a counterpart to Gaia16cfr in pre-outburst HST images.…”
Section: Introductionmentioning
confidence: 99%
“…For griz filters, the zeropoint was calculated from magnitudes of sources in the field taken from the SkyMapper Southern Survey (Onken et al 2019). For Johnson-Cousins filters, we used the tertiary standards in NGC 2442 presented by Pastorello et al (2009). In the case of the NIR data (JHK) we used sources taken from the Two Micron All Sky Survey (2MASS; Skrutskie et al 2006).…”
Section: Photometry With the Autophot Pipelinementioning
confidence: 99%
“…AT 2016jbu is situated to the south of NGC 2442, a spiral galaxy commonly referred to as the Meathook Galaxy. NGC 2442 has hosted two other SNe including SN 1999ga, a low luminosity Type II SN (Pastorello et al 2009) and SN 2015F, a Type Ia SN (Cartier et al 2017). We mark their respective locations in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…AT 2016jbu is located north of the southern distorted spiral arm of NGC 2442 and is still clearly present in NGC 2442 almost a year after maximum as seen in the white light image constructed from the datacube. The FOV (1 × 1 ) does however include the location of SN 1999ga (Pastorello et al 2009) as well as a luminous region in the center frame. This "Super-Bubble" has been noted by previous authors (Pancoast et al 2010), and is seen in the irregular kinematic pattern seen in the center of the FOV.…”
Section: Muse -Ing On the Local Environmentmentioning
confidence: 99%